AN ENVIRONMENTAL LAW STUDY ON ENVIRONMENTAL POLLUTION IN COASTAL AREAS - Anin Dita Tias Tata Yunarsa (Universitas Muhammadiyah Yogyakarta, 2012)
AN ENVIRONMENTAL LAW STUDY ON ENVIRONMENTAL POLLUTION IN COASTAL AREAS